Are you sure we're talking about the same person? different professional perspectives on a single patient : challenges for an integrative approach within the primary mental health care system - Brandt, Anneliese (Department of Psychology, 2023)
In 1999 a system of placing intern psychologists in primary health care centres was introduced by the Department of Psychiatry of the University of Cape Town. This allowed interns the opportunity of experiencing and evaluating psychiatric services in situ at clinic level within the primary mental health care system. My own experience as an intern working at a clinic served to highlight some areas of difficulty in offering an integrated approach at a primary level. They are in particular the different perspectives brought to the provision of mental health care by the professionals, and the inequalities in status and work conditions of the partners in mental health care service provision. The differing professional perspectives and their implications for case management are explored through a case study of a single patient and her experience of the service. The study illustrates the way in which effective service provision may be compromised by the inherent differences in the perspectives of the disciplines represented by the professionals, as well as by the failure to recognise the extent and importance of the role played by the psychiatric nursing personnel. It is suggested that the system could be significantly improved by the introduction of a system of consultation between all of the partners to coordinate the care of patients in order to maximise the benefits they derive.